2015
DOI: 10.18632/oncotarget.6178
|View full text |Cite
|
Sign up to set email alerts
|

c-Maf regulates pluripotency genes, proliferation/self-renewal, and lineage commitment in ROS-mediated senescence of human mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are therapeutically relevant multilineage and immunomodulatory progenitors. Ex vivo expansion of these rare cells is necessary for clinical application and can result in detrimental senescent effects, with mechanisms still largely unknown. We found that vigorous ex vivo expansion of human adipose tissue-derived MSCs (hAMSCs) results in proliferative decline, cell cycle arrest, and altered differentiation capacity. This senescent phenotype was associated with reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 47 publications
0
33
1
Order By: Relevance
“…5). In addition to our laboratory's and others' work demonstrating how ROS and cellular senescence decrease the expression of c-MAF, a cofactor of RUNX2 [17,33], this study adds to the molecular understanding on how ROS and oxidative stress adversely impact on osteogenesis. Collectively, these reports highlight the importance of decreasing oxidative stress and ROS-levels which correlate strongly with age-for MSC osteogenesis to occur.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…5). In addition to our laboratory's and others' work demonstrating how ROS and cellular senescence decrease the expression of c-MAF, a cofactor of RUNX2 [17,33], this study adds to the molecular understanding on how ROS and oxidative stress adversely impact on osteogenesis. Collectively, these reports highlight the importance of decreasing oxidative stress and ROS-levels which correlate strongly with age-for MSC osteogenesis to occur.…”
Section: Discussionmentioning
confidence: 75%
“…2A). Conversely, expression levels of committed osteogenic genes such as collagen type 1a1 (COL1A1) [32] and the RUNX2 coactivator c-MAF [17,33] were decreased in C3H MSCs cultured in OM with exogenous H 2 O 2 treatment ( Fig. 2A).…”
Section: H 2 O 2 Enhances the Transcriptional Programme Of Adipogenesmentioning
confidence: 99%
“…A large number of studies have evaluated the ROS in cancer cells [185196] and their relationship with the mitochondrial activity [197208]. …”
Section: Mediterranean Diet and Cancermentioning
confidence: 99%
“…Moreover, although Li et al demonstrated that MSCs derived from old donors showed a more rapidly decreased survival rate than MSCs derived from young donors in the infarct region in acute myocardial infarction (MI) model, N‐acetyl‐L‐cysteine (NAC) which is a ROS scavenger can protected MSCs derived from old donors from apoptosis in vivo and significantly enhanced the therapeutic effects of MSCs. Long‐term culture always results in proliferative decline, cell cycle arrest and decreased differentiation capacity in adipose‐derived MSCs by ROS‐induced suppression of c‐Maf . However, long‐term culture of umbilical cord blood‐derived MSCs reinforces senescence by activating p38, MAPK, and p53/p21 pathways and enhancing ROS generation .…”
Section: Antioxidative Capacities Of Senescent and Apoptotic Mscsmentioning
confidence: 99%
“…Various conditions including ageing, long-term culture and H 2 O 2 , adverse oxygen content, high glucose, proinflammatory cytokines and other toxic factors, abnormally up-regulated ROS production can harm MSC activities. 22,[29][30][31][32][33] On the other hand, although MSCs play critical roles on immunomodulatory properties for therapy in various diseases, the constant isolation from donors also bring out unrecoverable injury. 34…”
mentioning
confidence: 99%